After Sochi 2014: costs and impacts of Russia`s Olympic Games - Müller, M. (Eurasian Geography and Economics, 2015)
This paper assesses the outcomes of the 2014 Winter Olympic Games in Sochi, Russia, examining the costs and economic impacts of the event, the prospects for the long-term use of venues and infrastructure, and the attitudes of the global and the Russian population. Total costs were $55 billion, having increased 4.5 times from $12 billion at the time of the bid. Of this total, about $16 billion were sports-related costs. After accounting for inflation, this makes Sochi the second-most expensive Olympics ever in terms of sports-related costs and the most expensive Olympics in terms of cost per event. With a public share of 96.5 percent of funding, the Sochi Games had the highest proportion of public money for any Olympic Games on record. The benefit from this high cost, however, is limited. Extensive construction led to hotel overcapacities, investors defaulted on state-backed loans, and there is no coherent plan for the after use of venues and some of the largest infrastructure projects. As a consequence, the Sochi Olympics will continue to be a burden for the Russian state, with expenses for operation, maintenance, and foregone interest and tax revenue in the order of $1.2 billion per year. The event also did not manage to improve the image of Russia in the world. Among the domestic population, support dropped over the seven years of its implementation, most notably among the local population.